2012
DOI: 10.1590/s0103-21002012000200020
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre conhecimento, atitude, escolaridade e tempo de doença em indivíduos com diabetes mellitus

Abstract: Objectives: To relate the knowledge and attitudes of users with type 2 diabetes mellitus (DM2), according to educational level and duration of disease. Methods: This was a quantitative, descriptive transversal study conducted in a Basic Health District Unit in the municipality of Ribeirão Preto, SP, in 2010. We interviewed 123 users with DM2, who met the inclusion criteria. For data collection we used: Knowledge Questionnaire (DKN-A) and Questionnaire of Psychological Attitudes about Diabetes (TA-19). Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
2
66

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 19 publications
(21 reference statements)
5
40
2
66
Order By: Relevance
“…A study conducted in Brazil identified increased knowledge of the participants on DM after participation in an educational program, however, this result was not reflected in increased attitude to the most appropriate coping strategies with the disease. (26) Authors suggested that education and disease duration can influence their attitudes, (16) however, in this study there was no significant correlation between these variables.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…A study conducted in Brazil identified increased knowledge of the participants on DM after participation in an educational program, however, this result was not reflected in increased attitude to the most appropriate coping strategies with the disease. (26) Authors suggested that education and disease duration can influence their attitudes, (16) however, in this study there was no significant correlation between these variables.…”
Section: Discussioncontrasting
confidence: 53%
“…(12) Knowledge can be defined as a set of information that the individual needs to learn to manage their health condition. (16) To assess the knowledge, we used the Diabetes Knowledge Scale (DKN-A). This is a self-administered questionnaire containing 15 questions, with multiple choice answers on the various aspects related to general knowledge of DM.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations